Orientation to Sustainable and Climate Adapted Agriculture with Advanced Technology in Industry 4.0 in Vietnam - Cuong, Nguyen Hung; Dung, Do Thi; Duy, Do Khanh; Huong, Do Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 37 No 1, 2021)
In recent years, the rural agricultural economy in Vietnam has experienced outstanding shifting progress. The paper focuses on analyzing and evaluating an overview of the agricultural economy in Vietnam in the context of global climate change and global integration during industry 4.0. The results show that many advanced and modern models of association and cooperation which are effective in agriculture and rural areas have been applied to increase production efficiency. Science and technology applied to agriculture will increase the value of the agricultural sector in Vietnam. The innovations and prosperity of agricultural infrastructure combined with the implementation of the national scheme on restructuring agricultural sectors oriented to added value increase and sustainabe development will lead to a sustainable and climate adapted agriculture.